GOOD GOVERNANCE IMPLEMENTATION IN REALIZING QUALITY OF PUBLIC SERVICES WITH INTEGRITY - Mohammad Redy; Zainurrafiqi Zainurrafiqi (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
The  purpose  of  this  study  was  to  determine  the  effect  of  the  implementation  of  good  governance  on  the  quality  of public  services  at  the  Department  of  Population  and  Civil  Registration  of  Pamekasan  Regency.  This  research  is classified as explanatory research with a quantitative approach. The sample used was 95 respondents with purposive sampling technique. The type of data used is primary data, namely data collection using a questionnaire. Analysis of the  data  used  is  Linear  Regression  with  SPSS.  The  results  of  this  study  indicate  that  the  application  of  good governance  has  a  positive  effect  on  the  quality  of  public  services  at  the  Department  of  Population  and  Civil Registration of Pamekasan Regency.